2007
DOI: 10.1111/j.1525-1438.2006.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of adnexal masses: risk of malignancy index, ultrasonography, magnetic resonance imaging, and radioimmunoscintigraphy

Abstract: A risk of malignancy index (RMI), based on menopausal status, ultrasound (US) findings, and serum CA125, has previously been described and validated in the primary evaluation of women with adnexal masses and is widely used in selective referral of women from local cancer units to specialized cancer centers. Additional imaging modalities could be useful for further characterization of adnexal masses in this group of women. A prospective cohort study was conducted of 196 women with an adnexal mass referred to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…Morgante et al [5] in 1999 found that RMI 2 was more reliable in discriminating benign and malignant ovarian disease than RMI 1. In a study by Van Trappen et al [12], analysis of 123 patients managed sequentially, using RMI cut off values of C25 and \1,000 and then US and MRI provided a sensitivity of 94 % and a specificity of 90 %. In our study, a ROC analysis has shown that at a cut off value of 25 the likelihood of having malignant disease is 1.46, while at cut off level of 1,000 the likelihood is 24.11 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Morgante et al [5] in 1999 found that RMI 2 was more reliable in discriminating benign and malignant ovarian disease than RMI 1. In a study by Van Trappen et al [12], analysis of 123 patients managed sequentially, using RMI cut off values of C25 and \1,000 and then US and MRI provided a sensitivity of 94 % and a specificity of 90 %. In our study, a ROC analysis has shown that at a cut off value of 25 the likelihood of having malignant disease is 1.46, while at cut off level of 1,000 the likelihood is 24.11 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the RMI will help to categorise patients into those with a high likelihood of malignancy and those very unlikely to have an ovarian malignancy, thus determining the course of action. However, up to 20% of masses detected by ultrasound remain indeterminate [6][7][8]. It is of great importance to characterise an adnexal mass as accurately as possible to guide appropriate management as treatment options become more sophisticated and patient-specific [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al [12], who created their own model of a malignancy risk index, added the parameter of tumor size (S) to the RMI, and have termed it RMI 4. Retrospective and prospective validation of the four versions of the RMI have been conducted in different clinical studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], where a cutoff value of 200 for RMI 1-3 and 450 for RMI 4 showed the best discrimination between benign and malignant pelvic masses, with high levels of sensitivity and specificity (sensitivity 51%-90%, specificity 51%-97%). The main advantage of four RMIs is that it is a simple scoring system that can be applied directly into clinical practice without the introduction of expensive or complicated methods (such as computed tomography scan, magnetic resonance imaging, and wholebody positron emission tomography).…”
Section: Jung-woo Park Et Al Four Rmis In Pelvic Massesmentioning
confidence: 99%